The Prevalence of Intimate Partner Violence and Victim Resources at Georgia Southern University - Lacey, Elizabeth (2020)
The goal of this project is to measure the prevalence of intimate partner violence (IPV) among young adults in a college setting. Using an anonymous, self-report survey, college students at a large university in the south were asked about their experiences with IPV, as well as their knowledge and perceptions of victim’s services available on campus and in the community. Results reveal that IPV Is more prevalent among females and technology-related IPV is more prevalent among males at Georgia Southern University. In addition, the study found that compared to women, men are more informed about existing victim services